Track design handbook for light rail transit (Transportation Research Board, 2012)
TCRP report 155 provides guidelines and descriptions for the design of various common types of light rail transit (LRT) track. The track structure types include ballasted track, direct fixation ("ballastless") track, and embedded track. The report considers the characteristics and interfaces of vehicle wheels and rail, tracks and wheel gauges, rail sections, alignments, speeds, and track moduli. The report includes chapters on vehicles, alignment, track structures, track components, special track work, aerial structures/bridges, corrosion control, noise and vibration, signals, traction power, and the integration of LRT track into urban streets.
At head of title: Transit Cooperative Research Program.
Keywords: Street-railroad tracks -- Design and construction.; Railroad tracks -- Design and construction.; Street-railroad tracks -- United States -- Handbooks, manuals, etc.; Street-railroads -- United States -- Design and construction -- Handbooks, manuals, etc.; elektronické knihy; electronic books